2016
DOI: 10.1186/s40560-016-0141-8
|View full text |Cite|
|
Sign up to set email alerts
|

Neurocritical care update

Abstract: This update comprises six important topics under neurocritical care that require reevaluation. For post-cardiac arrest brain injury, the evaluation of the injury and its corresponding therapy, including temperature modulation, is required. Analgosedation for target temperature management is an essential strategy to prevent shivering and minimizes endogenous stress induced by catecholamine surges. For severe traumatic brain injury, the diverse effects of therapeutic hypothermia depend on the complicated pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 110 publications
(140 reference statements)
0
11
0
4
Order By: Relevance
“…22,29 Therefore, decisions regarding treatment policy, especially in cases with severe aneurysmal SAH, are extremely important, not only from the viewpoint of patient outcome but also medical economy. 14,25 Excessive catecholamine secretion, such as epinephrine and norepinephrine, occurs in the majority of aneurysmal SAH cases, causing sympathetic nervous system activation especially in severe cases, 12,19,20 resulting in the occurrence of systemic complications such as pulmonary cardiac lung edema, arrhythmia, or heart failure, 11,21,28 and reflect the primary brain injury itself. Yokobori et al 32 reported that serum BNP was significantly correlated with SAH grading and was a useful biomarker of systemic clinical impact, reflecting increased cardiac preload and afterload in severe aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%
“…22,29 Therefore, decisions regarding treatment policy, especially in cases with severe aneurysmal SAH, are extremely important, not only from the viewpoint of patient outcome but also medical economy. 14,25 Excessive catecholamine secretion, such as epinephrine and norepinephrine, occurs in the majority of aneurysmal SAH cases, causing sympathetic nervous system activation especially in severe cases, 12,19,20 resulting in the occurrence of systemic complications such as pulmonary cardiac lung edema, arrhythmia, or heart failure, 11,21,28 and reflect the primary brain injury itself. Yokobori et al 32 reported that serum BNP was significantly correlated with SAH grading and was a useful biomarker of systemic clinical impact, reflecting increased cardiac preload and afterload in severe aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Initial treatment consists of administration of a benzodiazepine by emergency medical services or an emergency department, and care of SE patients quickly transfers to intensive care units (ICUs). If the initial benzodiazepine treatment and subsequent treatment with intravenous antiepileptic drugs (AEDs) such as phenytoin, levetiracetam, valproate, or lacosamide fail to stop the seizures, the patient is defined as having refractory SE (RSE), which is treated with third‐line anesthetic agents, such as propofol, high‐dose midazolam, or barbiturates.…”
mentioning
confidence: 99%
“…Unfortunately, the original version of this article [ 1 ] contained several errors: Reference 24 in the original article (reference [ 2 ] in this erratum) should have been “Brophy GM, Human T, Shutter L. Emergency neurological life support: pharmacotherapy. Neurocrit Care.…”
Section: Erratummentioning
confidence: 99%